Impact of Long Working Hours on Office Workers - Wicaksono, Muhammad Yusuf Adityas (BKM Public Health and Community Medicine, 2024)
Purpose: This study analyzes the factors and impacts of long working hours on office workers. The focus is on understanding how prolonged working hours influence mental health and overall well-being. Methods: A literature review was conducted using scientific articles published between 2019 and 2024, with keywords "impact of overworking" and "psychosocial of office workers." Six articles that met the criteria were thoroughly analyzed. Results: The analysis revealed that overworking or work fatigue caused by long working hours has several negative effects on office workers' mental health. Although extended working hours can lead to a sense of accomplishment for some workers, they are often accompanied by mental fatigue and a loss of individual traits. The interconnectedness of these risk factors exacerbates the mental health issues and reduces the productivity of office workers. Conclusion: Long working hours negatively impact the mental health of office workers. Therefore, it is crucial to manage working hours effectively within the work environment to maintain the health and productivity of employees.